Pengaruh Edukasi Teknik Balut Tekan Terhadap Penghentian Perdarahan Pada Masyarakat Awam Di Kecamatan Tuminting Kelurahan Mahawu Lingkungan III Kota Manado - Ismawati Ismawati; Rahmat H. Djalil; Zainar Kasim (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Bleeding is the most common cause of death where cases of open trauma are often found in the community, especially in traffic accidents and other accidents such as sharp object puncture wound. The purpose of this research was to find out the effect of pressure bandage education on knowledge and attitude of stopping bleeding in ordinary people in the 3rd Neighborhood Mahawu Village, Tuminting Subdistrict, Manado. This research was conducted by using a quasy experimental method (one group prettest and posttest design). Samples were amounted to 15 respondents taken by a random sampling. The instruments used in this research was questionnaire. Then, the collected data was processed by running the SPSS computer program version 16.0 to be analyzed by a Mc Nemar test with the significance level ? = 0,05. The Mc Nemar test result showed the value of knowledge ? = 0,002 which was smaller than ? = 0,05, meaning Ha is accepted or education in pressure bandage techniques can influence the attitude of ordinary people. The conclusion of this research is that there is an effect of pressure bandage education on knowledge and attitude of stopping bleeding in ordinary people in the 3rd Neighborhood Mahawu Village, Tuminting Subdistrict, Manado. It is suggested so that the community can get education with pressure bandage material to increase knowledge, attitudes and reduce the risk of bleeding that occurs.